Multilingual Students’ Translingual Practices During Classes of English as a Foreign Language: Attitudes of Polish and German EFL Teachers - Hadrian Lankiewicz; Sylwia Adamczak-Krysztofowicz; Grzegorz Lisek (Polilog: Studia Neofilologiczne)
This paper focuses on the challenges in educational area or, more precisely, we narrow down our considerations to the context of teaching English as a foreign language (EFL). Research on multilingualism points to the need for a heteroglossic approach to language use in educational process [García, Leiva 2014]. The aim of our research is to delve into the mindset of EFL teachers regarding (1) their acceptance of translingual practices during an EFL class taught to plurilinguals, (2) the articulation of potential benefi ts or drawbacks for the language learning process aﬀ ected by translingual practices, and, ultimately, (3) the perception of these practices with reference to TCLA (teacher critical language awareness). The obtained data shows an interesting picture of teaching EFL in the multilingual context of mixed nationality students. Both Polish and German teachers of EFL seem to reach beyond the monolingual paradigm in the classroom. The majority of teachers can speak or understand additional languages to their native language and EFL. This may be construed as a potential for the strategic use of translanguaging for educational purposes and, ultimately, it is interpreted as a transformative quality of the language teacher in the education.